HBOC-301 in Porcine Kidney Normothermic Machine Perfusion and the Effect of Vitamin C on Methemoglobin Formation - Eileen Edgworth; Lisa Ernst; Zoltan Czigany; Turgay Saritas; Laura Sophie Zarnitz; Marc Wiartalla; Peter Boor; Eva Miriam Buhl; Rolf Rossaint; René H. Tolba; Benedict Doorschodt; Gregor Fabry; et al. (MDPI AG, 2022)
Normothermic machine perfusion (NMP) of kidneys in combination with an optimized perfusate composition may increase donor organ preservation quality, especially in the case of marginal donor grafts. Optimization of currently employed perfusates is still a subject of present research. Due to the advantages of being cell-free, easy to store, and having minimal antigenicity, hemoglobin-based oxygen carriers, such as HBOC-301 (Oxyglobin®, Hemoglobin Oxygen Therapeutics LLC, Souderton, PA, USA), offer an alternative to the commonly used perfusates based on packed red blood cells (pRBC). As previously described, using HBOC results in formation of methemoglobin (metHb) as an adverse effect, inducing hypoxic conditions during the perfusion. As a potential counterpart to metHb formation, the application of the antioxidant ascorbic acid (VitC) is of high interest. Therefore, this study was conducted in four experimental groups, to compare the effect of NMP with (1) HBOC or (3) pRBC, and additionally examine a beneficial effect of VitC in both groups (2) HBOC + VitC and (4) pRBC + VitC. All groups were subjected to NMP for 6 h at a pressure of 75 mmHg. Kidneys in the HBOC groups had a significantly lower renal blood flow and increasing intrarenal resistance, with reduced renal function in comparison to the pRBC groups, as demonstrated by significantly lower creatinine clearance and higher fractional sodium excretion rates. Clinical chemistry markers for tissue damage (LDH, lactate) were higher in the HBOC groups, whereas no significant histological differences were observed. Although the application of VitC decreased oxidative stress levels, it was not able to significantly increase the outcome parameters mentioned above in either group. This study demonstrated that HBOC-301 is inferior to pRBCs in our porcine kidney NMP model, independent of additional VitC administration. Oxidative stress and fragmentation of the hemoglobin polymers could be detected as a possible reason for these results, hence further research, focusing on the use of cell-free oxygen carriers that do not exhibit this complex of issues, is required.